ChemInform Abstract: A Comparison of the Solid‐State Structures of Halogen Azides XN3 (X: Cl, Br, I). Issue 13 (18th March 2013) - Lyhs, Benjamin; Blaeser, Dieter; Woelper, Christoph; Schulz, Stephan; Jansen, Georg
Abstract ClN3 is prepared by reaction of NaN3 with sodium hypochlorite and boric acid (‐196→+20 °C, 30 min) and its crystal structure is determined by single crystal XRD.